Entities of Chronic and Granulomatous Invasive Fungal Rhinosinusitis: Separate or Not?. (14th September 2018) - Zhou, Ling-Hong; Wang, Xuan; Wang, Rui-Ying; Zhao, Hua-Zhen; Jiang, Ying-Kui; Cheng, Jia-Hui; Huang, Li-Ping; Chen, Zhong-Qing; Wang, De-Hui; Zhu, Li-Ping
Abstract: Background: Chronic and granulomatous invasive fungal rhinosinusitis are important causes of blindness and craniocerebral complications. However, the classification of these 2 diseases remains controversial. Methods: We retrospectively analyzed patients with chronic and granulomatous invasive fungal rhinosinusitus in a Chinese tertiary hospital from 2009 to 2017, with a focus on classification and comparisons. Results: Among 55 patients enrolled in our study, 11 (11/55, 20%) had granulomatous invasive fungal rhinosinusitis (GIFRS) and 44 (44/55, 80%) had chronic invasive fungal rhinosinusitis (CIFRS). Aspergillus fumigatus and Dematiaceous hyphomycetes were identified in 2 patients with GIFRS. Compared with granulomatous type, CIFRS was more frequently encountered in immunocompromised patients ( P = .022), and the time from onset to diagnosis was much shorter ( P = .001). Proptosis and orbital apex syndrome showed no significant difference between granulomatous and CIFRS in our study. The treatment options and prognosis of both diseases also showed no significant difference. Conclusions: Despite the consensus on histopathology, the classification of the chronic and granulomatous types may need further evaluation in clinical considerations.